Dicarboxylic Acid Excretion in Normal Formula‐Fed and Breastfed Infants. (6th May 2016) - Anderson, Maria; Eliot, Kathrin; Kelly, Patrick; Shoemaker, James
Abstract : Purpose: Infant formulas are often supplemented with medium‐chain triglycerides (MCTs) to optimize calories for small for gestational age or preterm infants. High amounts of MCTs have been associated with an increase in dicarboxylic acid (DCA) in the urine. Elevated DCA in the urine is also a clinical indicator for fatty acid metabolism disorders. The purpose of this study was to identify if there is an amount of MCTs that can be provided without elevating urinary DCA excretion. Methods: A metabolic screening laboratory provided urinary DCA excretion data for 175 infants. It was verified that no infants were diagnosed with metabolic disorders and therefore were considered "metabolically normal." All infants were either formula fed or breastfed at the time of screening. The type and volume of formula provided at the time of urine screening was documented. The exact amount of MCTs provided to each infant was calculated. Results: The mean age of the infants was 3.09 months. The mean total DCA was determined for both the breastfeeding and formula groups. Within the formula group, the means were 32.07, 13.36, and 5.77 mmol/mol creatinine for adipic, suberic, and sebacic acids, respectively. Spearman correlation coefficient indicated correlations of r = 0.0693, r = 0.0166, and r = −0.0128 between percent MCT and adipic, suberic, and sebacic acids, respectively. No value was statistically significant. DCA excretion amounts did not vary between breastfed and formula‐fed infants. Our data suggest that clinicians should not expect elevated dicarboxylic aciduria in infants who are fed a standard formula without added MCT oil.